Exploring opportunities for coordinated responses to intimate partner violence and child maltreatment in low and middle income countries: a scoping review. (6th March 2017) - Bacchus, Loraine J.; Colombini, Manuela; Contreras Urbina, Manuel; Howarth, Emma; Gardner, Frances; Annan, Jeannie; Ashburn, Kim; Madrid, Bernadette; Levtov, Ruti; Watts, Charlotte
Abstract: Intimate partner violence (IPV) and child maltreatment (CM) by a parent or caregiver are prevalent and overlapping issues with damaging consequences for those affected. This scoping review aimed to identify opportunities for greater coordination between IPV and CM programmes in low- and middle-income countries (LMIC). Nine bibliographic databases were searched and grey literature was identified through the scoping review team. Eligible studies were published in English; described primary prevention programmes in LMIC that addressed IPV and CM, or addressed one form of violence, but reported outcomes for the other; reported IPV and CM outcomes; and evaluated with any study design. Six studies were identified published between 2013 and 2016 (four randomised controlled trials, one pre-post non-randomised study and one qualitative study). Programmes were based in South Africa (2), Uganda, (2), Liberia (1) and Thailand (1). All except one were delivered within parenting programmes. The emphasis on gender norms varied between programmes. Some parenting programmes addressed gender inequity indirectly by promoting joint decision-making and open communication between caregivers. Conclusions are tentative due to the small evidence base and methodological weaknesses. More robust evaluations are needed. Improved coherence between IPV and CM programmes requires equal attention to the needs of women and children, and the involvement of fathers when it is safe to do so.